2019
DOI: 10.1038/s12276-019-0218-2
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry-based proteome profiling of extracellular vesicles and their roles in cancer biology

Abstract: Over the past three decades, extracellular vesicles (EVs) have arisen as important mediators of intercellular communication that are involved in the transmission of biological signals between cells to regulate various biological processes. EVs are largely responsible for intercellular communication through the delivery of bioactive molecules, such as proteins, messenger RNAs (mRNAs), microRNAs (miRNAs), DNAs, lipids, and metabolites. EVs released from cancer cells play a significant role in signal transduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 109 publications
1
88
0
Order By: Relevance
“…Recent studies have demonstrated that EV surface proteins bear characteristics of their tissue of origin and these EVs can be captured from bodily fluids using antibody-based assays targeting these proteins [ 29 , 30 ]. Proteomic profiling of EVs is a novel and sensitive approach to increase understanding of EV function and its use has been successful in unravelling their role in cancer [ 31 ]. A proteomic approach will also reveal potential protein biomarkers for isolating tissue-specific EVs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that EV surface proteins bear characteristics of their tissue of origin and these EVs can be captured from bodily fluids using antibody-based assays targeting these proteins [ 29 , 30 ]. Proteomic profiling of EVs is a novel and sensitive approach to increase understanding of EV function and its use has been successful in unravelling their role in cancer [ 31 ]. A proteomic approach will also reveal potential protein biomarkers for isolating tissue-specific EVs.…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota can secrete different types of EVs, including outer membrane vesicles (OMVs), shedding vesicles, and apoptotic bodies 8,9 . EVs are mainly composed of lipids, proteins, nucleic acids, and metabolites [10][11][12] . Although the underlying mechanisms are still unclear, their primary role is to transport active biomolecules into cells over long distances, providing drug delivery to target sites or regulating host cellular responses 11,13 .Recent studies have provided mechanistic evidences for the participation of the gut flora in CRC development.…”
mentioning
confidence: 99%
“…c-MYC activation induces glycolysis which facilitates lactate production (67) and mTOR pathway drives anabolic metabolism (58,59,68). All these oncogenic proteins have been reported in tumor EVs (69) and could be influencing these metabolic pathways in the recipient neighboring glioma cells to favor progression. Recent studies showed that large oncosomes/ large EVs preferentially contain protein cargo targeted to mitochondrial metabolic processes including VDAC1/2, the solute carriers SLC25A6 and SLC25A5 that are mitochondrial ADP/ATP translocators as well as the ATP synthase subunit ATP5B.…”
Section: Glioma Ev Mediated Reprogramming Of Metabolic Activitymentioning
confidence: 99%